Budaya Kualitas Pada Organisasi Yang Berkualitas - Damayanti, Retno Wulan (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2007)
One of the biggest barier which faced by company to apply total quality is cultural barricade. Many company try to implement total quality , entangling employees at all level with providing training to guarantee employees to be skilled, where this matter is done just to flatten their ability. There is no effort to make a freshment in doing something. In other words, there is no effort to change company culture.